2003
DOI: 10.1002/clc.4960261106
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of simvastatin and atorvastatin on high‐density lipoprotein cholesterol and apolipoprotein A‐I are consistent across hypercholesterolemic patient subgroups

Abstract: SummaryBackground: In addition to lowering plasma levels of lowdensity lipoprotein cholesterol (LDL-C), statins also raise high-density lipoprotein cholesterol (HDL-C).Hypothesis: Recent studies have shown that treatment with simvastatin results in larger increases in HDL-C than those seen with atorvastatin. The results of three clinical studies are analyzed, comparing the effects of simvastatin and atorvastatin on HDL-C and apolipoprotein A-I (apo A-I) in the total cohort and in several subgroups of hyperchol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…Patients who were started on statin therapy or had undergone doubling of a statin dose experienced a decrease in HDL-C levels. This unexpected effect was also reported in other studies [18,19]. The results of three randomized, multicenter clinical studies comparing the effects of atorvastatin and simvastatin on HDL-C were analyzed by Davidson et al (2003); who found that both drugs increased HDL-C consistently at low doses but at higher doses, simvastatin retained its raising effect on HDL-C while atorvastatin showed a negative dose response pattern [18], this may explain our results bearing in mind that majority of our study population were on atorvastatin.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Patients who were started on statin therapy or had undergone doubling of a statin dose experienced a decrease in HDL-C levels. This unexpected effect was also reported in other studies [18,19]. The results of three randomized, multicenter clinical studies comparing the effects of atorvastatin and simvastatin on HDL-C were analyzed by Davidson et al (2003); who found that both drugs increased HDL-C consistently at low doses but at higher doses, simvastatin retained its raising effect on HDL-C while atorvastatin showed a negative dose response pattern [18], this may explain our results bearing in mind that majority of our study population were on atorvastatin.…”
Section: Discussionsupporting
confidence: 75%
“…This unexpected effect was also reported in other studies [18,19]. The results of three randomized, multicenter clinical studies comparing the effects of atorvastatin and simvastatin on HDL-C were analyzed by Davidson et al (2003); who found that both drugs increased HDL-C consistently at low doses but at higher doses, simvastatin retained its raising effect on HDL-C while atorvastatin showed a negative dose response pattern [18], this may explain our results bearing in mind that majority of our study population were on atorvastatin. Moreover, we noticed that patients who experienced transient reductions in HDL-C level experienced an increase afterwards which can be attributed to distributing brochures on life style modifications that can help increase HDL-C levels; however, we were not able to measure this effect due to study duration.…”
Section: Discussionsupporting
confidence: 75%
“…One possible explanation is the relatively greater increase in HDL cholesterol in patients treated with high-dose simvastatin compared with those treated with high-dose atorvastatin, a finding consistent with previous studies. 16,17 Patients who have survived 4 months after ACS without a recurrent event could be considered to be patients with "stable coronary artery disease (CAD)." Data from the Treating to New Targets (TNT) and the Incremental Decrease in End points through Aggressive Lipid lowering (IDEAL) trials are consistent with the findings 18,19 in the chronic phases of A to Z and PROVE IT.…”
Section: Long-term Benefitmentioning
confidence: 99%
“…Whilst statins are able to reduce LDL cholesterol levels by 40% or more, their effects on HDL cholesterol levels are much more limited with elevations in efficacy trials usually reported to be in the 5-15% range [1][2][3]. Use of these agents in long term clinical trials has generally resulted in increases toward the lower end of this range.…”
Section: Hmg Coa Reductase Inhibitorsmentioning
confidence: 95%